Physical exercise and bedtime procrastination among college students: mediating roles of self-control and mobile phone addiction - Wang, Yangping; Wang, Xudong; Wu, Shanshan; Zhang, Weijie; Li, Jingjing; Liu, Bing (Frontiers in Psychology, 2025)
BackgroundSleep is a crucial foundation for maintaining both physical and mental health. Bedtime procrastination has been identified as a significant behavioral factor contributing to decreased sleep quality. Research has identified bedtime procrastination as a prevalent issue among college students, posing significant challenges to their overall health. Regular physical exercise, as a positive lifestyle intervention, may mitigate procrastination behaviors. However, the specific effects of physical exercise on bedtime procrastination among college students, as well as the underlying mechanisms, remain unclear and warrant further investigation.ObjectiveThis study aims to examine the effects of physical exercise on bedtime procrastination in college students and to analyze the mediating roles of self-control and mobile phone addiction.MethodsA total of 1,000 college students from four universities were surveyed using the Physical Activity Rating Scale (PARS-3), the Bedtime Procrastination Scale (BPS), the College Student Self-Control Scale (CSSCS), and the Mobile Phone Addiction Index (MPAI) through online questionnaires.Results(1) Physical exercise was positively correlated with self-control (p < 0.001) and negatively correlated with mobile phone addiction (p < 0.001). Moreover, a significant negative association was identified between self-control and both mobile phone addiction and bedtime procrastination among college students (p < 0.001). Furthermore, mobile phone addiction was positively correlated with bedtime procrastination (p < 0.001). (2) The total effect of physical exercise on bedtime procrastination was significant (β = −0.137, 95% CI = [−0.191, −0.083]); moreover, physical exercise alleviated bedtime procrastination through a chain mediation effect involving self-control and mobile phone addiction (β = −0.019, 95% CI = [−0.032, −0.010]), indicating that physical exercise mitigated mobile phone addiction by fostering self-control, thereby alleviating bedtime procrastination.ConclusionPhysical exercise significantly reduces bedtime procrastination among college students. Self-control and mobile phone addiction serve as mediators in the relationship between physical exercise and bedtime procrastination.